Dependence of Life Expectancy of the Population on the Well-Being of the Country (International Statistical Study) - Fal’tsman, V. K. (Stud Russ Econ Dev, 2021)
The article examines the results of processing statistical data for 180 countries of the world, on the basis of which a welfare scale is built, which characterizes the increase in life expectancy of the population as GDP (PPP) and healthcare costs grow. The scale is used to predict the life expectancy of the Russian population.